Cutting equipment for heat supply pipeline production - LI LEIGANG; XUE LIJUAN; WU HONGYU; SUN HAITAO; WU GUOKAI; XIAO XIANBIN; WANG CHUNLIANG; WU RUHUI; XIAO DONGHONG (2024)
The utility model discloses cutting equipment for heat supply pipeline production, and relates to the field of cutting equipment. Comprising a supporting frame body, a positioning base is fixedly installed at the upper end of the supporting frame body, a positioning supporting column is fixedly installed at the front end of the positioning base, a blocking plug is fixedly installed at the tail end of the positioning supporting column, a blocking ring is arranged on the edge of the blocking plug, a rotating mechanism is movably installed on the positioning base, and a sliding ring is fixedly installed on the inner side of the rotating ring. A rotating frame is fixedly mounted on the outer side of the rotating ring, a mounting groove is formed in the rotating frame, a crank is fixedly mounted on the rotating frame, and a cutting mechanism is arranged at the tail end of the rotating frame. After the crank is rotated, the cutting blade can rotate along the outer wall of the pipeline so as to cut the pipeline, the